Studi literatur mengenai anak usia sekolah dasar dengan ADHD: Perspektif neuropsikologi - Sadida, Qaulan; Tunliu, Sarlina K; Fatimah; Kartikasari, Novia; Asmaradhani, Debrinna T (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
ADHD is a neurological developmental disorder that mostly affects children. Its characteristics in the form of inattention, disorganization and hyperactivity-impulsivity make it difficult for children to think and behave typically at home and at school. Researchers conducted a literature review on brain disorders in elementary school-aged children with ADHD to determine the level of damage and deviations that occurred. The method used was an integrative literature review using the PRISMA technique to extract 10 relevant articles from the Scopus and PubMed databases. The result is that the parts of the brain affected are the frontal, prefrontal, parietal, temporal, caudate, gyrus, cerebellum, and networks found in the brain such as the salience network, default mode network, and dorsal attention network. Elementary school age children (6 - 15 years) who have ADHD, regardless of sub-type, are prone to experiencing difficulties in sustained attention, response inhibition, memory and decision making. Parents and teachers are expected to help children's growth and development with disciplinary interventions such as understanding ADHD, collaboration with parties who frequently interact with children, consistent routines, a conducive environment, and positive reinforcement.